Organization structure, contract design and government ownership: A clinical analysis of German privatization - Dyck, I.J.Alexander; Wruck, Karen Hopper (Journal of Corporate Finance, 1998)
This paper examines the role that organization structure and contract design played in resolving economic and political problems that arose during Germany's privatization process. We find that German officials structured organizations and contracts in a way that made credible the government's commitment to rapid privatization. This credibility served to protect the process from political and social opposition. In addition, it enabled Germany to attract talented private sector managers to its privatization effort. This began with the establishment of an independent privatization agency, the Treuhand. It culminated with the creation of another set of independent organizations called Management KGs, to which the Treuhand outsourced part of its restructuring, management and privatization work.